Comparative Study of the Nutritional Value of Four Types of Egyptian Palm Pollens - Mokhtar Bishr; Samar Y. Desoukey (Journal of Pharmacy and Nutrition Sciences, 2012)
Pollen grains are good sources of vitamins, minerals and amino acids with a high nutritional value that can be used as human food supplement. Date palm pollens are used in the Middle East especially Egypt in herbal mixtures as a folk medicine remedy for curing male infertility and promoting fertility in women .The raw materials purchased from the market are found to be a mixture of several palm pollens. The main objective of this study was to determine the nutritional value of four local Egyptian date pollen grains Amhat(A), Hiani(H), Sewy(S)& Zaghlol(Z) by microscopical and chemical means. These differences could determine the quality of separate pollen grains and show to what extent they affect the quality of the natural products manufactured from them? Each of the pollen samples were treated identically: collected from locations of similar clay loamy soils, in March 2011 at an early time of the day, subjected to electron microscope examination and chemical analysis of trace elements, amino acids & vitamins. The results showed that there are clear differences in the quality of the four Egyptian palm pollens which could be distinguished microscopically and chemically by the percentage of the trace elements, amino acids & vitamins.